Development of Storybook to Improve Early Children's Reading Ability - Aip Saripudin (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
Abstract Early childhood reading skills are focused on recognizing reading materials such as magazines, daily journals, children's activity books, books of picture, animal series books, and other books that can improve children's early reading skills. This is rarely understood by some PAUD teachers in Indonesia, resulting in misunderstandings in learning activities. This research aims to develop children's story book by themes as an effort to stimulate early childhood reading skills. Another goal is to find out the feasibility of using children's story books by themes as an effort to stimulate early childhood reading skills. The methode of research used is research and development which is modified from the model developed by Borg and Gall. The research development procedure is carried out through six stages, (a) Collect of information (b) compiling product designs (c) product validation developed (d) product design improvements (e) limited product trials and (6) product results of children's story books. This research resulted in 3 children's story books entitled “Ikan Koi Si Penolong”, “Aku membantu Ayah”, and “Belanja bersama Ibu